An intelligent control of NH3 injection for optimizing the NOx/NH3 ratio in SCR system. Issue 5 (October 2019) - Liu, Guofu; Bao, Wenyun; Zhang, Wei; Shen, Dekui; Wang, Qi; Li, Chao; Luo, Kai Hong
Abstract: The distribution of nitrogen oxides (NOx ) flux within the cross-section area in front of ammonia injection grid (AIG) under different operating conditions was obtained by computational fluid dynamics (CFD) method. Weight of NOx flux in the sub-zone corresponding to each of the ammonia (NH3 ) injection branch-pipes of AIG system was analyzed and the sensitivity of which against the plant power load was figured out. A number of "critical" ammonia injection branch-pipes were determined with regard to the weight sensitivity analysis. The selected "critical" branch-pipes were changed to be controlled by the automatic valves, and an intelligent tuning strategy was proposed. The NOx /NH3 mixing stoichiometry over the cross-section area in front of AIG system was significantly modified for the high utilization ratio of ammonia. A case work was launched on the selective catalytic reduction (SCR) system of a 660 MW plant. As a result, the ammonia consumption rate (ACR) was found to be reduced by 6.44% compared to that under previous control system, and was 9.31% lower than that of the unapplied system. The methodology for determining the "critical" branch-pipes and intelligent tuning strategy of ammonia injection notably saved the ammonia consumption of SCR system, and the formation of ammonium bisulfate (ABS) were greatly confined. Graphical abstract: Image 1 Highlights: Weight of NO x flux in sub-zone of section-cross area in front of AIG was analyzed. The "critical" NH3 injection branch-pipes were determined for intelligent control. NOx /NH3 ratio in SCR system can be optimized via application of this technology.